A study on respiratory morbidities and pulmonary functions among traffic policemen in Bengaluru city - Giriyanna Gowda; R Thenambigai (Wolters Kluwer Medknow Publications, 2020)
Context: Air pollution is a major public health problem in the present Indian cities, due to unplanned urbanization and increased use of vehicles. Traffic policemen, due to the nature of their job and working atmosphere, are more prone to develop respiratory problems such as asthma, chronic obstructive pulmonary disease, rhinitis, recurrent respiratory tract infections, and others. Objectives: The objective was to find out the respiratory morbidities and to assess their pulmonary function using computerized spirometry among traffic policemen in Bengaluru city. Settings and Design: A cross-sectional study was conducted for a period of 6 months (from January 2018 to June 2018) in randomly selected traffic police stations in South Bengaluru, Karnataka. Subjects and Methods: A pretested, semi-structured questionnaire was used to collect information on the demographic profile, duration of exposure, smoking history, allergy/asthma history, and the use of personal protective measures. Pulmonary function test (PFT) was done to assess the lung function using computerized spirometry. Statistical Analysis Used: Data were entered and analyzed using Microsoft Excel 2016 version. Results: A total of 217 traffic policemen were included in the study. The mean duration of working in the traffic department was 5.9 ± 6.6 years (mean ± standard deviation). Among them, 101 (46.5%) used personal protective measures. Allergic rhinitis was reported by 38 (17.5%) individuals, and 28 (12.9%) individuals had chest symptoms (cough and breathing difficulty). Among them, 44 (20.3%) experienced exacerbation of these symptoms at the workplace. Observed mean values of all parameters in the PFT were less than their predicted (expected) values. Conclusions: There was increased burden of respiratory problems and lower lung volumes and flows among traffic policemen.